DEM analysis of micromechanics and buffering capacity of superquadric mixture granular materials under impact load - Qiu, Hongzhi; Yuan, Jintao; Han, Peifeng; Yang, Miao; Huang, Wenyao; Fang, Xu; Li, Yuxin (Frontiers in Earth Science, 2022)
As one of the most common geological disasters, rockfalls seriously threaten the safety of linear projects such as roads, railways, and oil and natural gas pipelines. The rigid protective structures that are used for disaster reduction are easily damaged by the impact of rockfalls, which affects the service life of structures. Consequently, the buffer layer has been introduced to resolve this problem. In this work, numerical simulations were carried out by the discrete element method to study the interaction between falling rocks and the granular medium of a soil cushion layer that is installed on a rigid structure. The falling rock is modeled as a single sphere and the soil cushion layer is modeled as a component composed of a collection under the action of gravity, where the filled particles of the soil cushion layer are based on superquadric spheres generated by the superquadric surface equation. This paper uses three shapes (i.e., spheres, cubes, and cylinders) to mix and match as the soil cushion layer. The buffer performance of different mixed material buffer layers is investigated by analyzing the pressure of the bottom plate. The force chain propagation process is investigated by analyzing the comparison of the force chains of the soil cushion layers with different thickness and different filling particles after being impacted. The energy propagation process was studied by analyzing the evolution of the kinetic energy of the particles after the impact of the soil cushion layer.